The next ten years in neonatology: new directions in research - Fanos, Vassilios; Mussap, Michele; Faa, Gavino; Papageorgiou, Apostolos (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2014)
This paper is a prelude to proceedings of the 10th International Workshop on Neonatology to be held in Cagliari, Italy from October 21st to 25th, 2014. These proceedings will be a significant milestone, highlighting the new frontiers of perinatal and neonatal research. Over the five days of this meeting, we aim to (1) examine the roots of the new directions in perinatal and neonatal research; (2) predict the trajectories of advancement in medical technologies, research, clinical care and teaching that will be the future of perinatology and neonatology. The discussion will be in four sections: back to the future: the placenta and perinatal programming; paradigm shift: the revolution of metabolomics in perinatalogy and neonatology; brave new world: the microbiome and microbiomics from perinatal to adult life; new inhabitants on the planet earth: adults who were born with extremely low birth weight. Proceedings of the 10th International Workshop on Neonatology · Cagliari (Italy) · October 22nd-25th, 2014 · The last ten years, the next ten years in Neonatology Guest Editors: Vassilios Fanos, Michele Mussap, Gavino Faa, Apostolos Papageorgiou